Anti-Acne Activity of Robusta Green Coffee Bean Extract against Cutibacterium acnes - Putri, Cinthiya Ekwinta; Puspitasari, Ismi; Novita, Mega; Marlina, Dian (Fakultas Farmasi, Universitas Surabaya, 2025)
Acne vulgaris, a common chronic skin disorder, is primarily caused by the overgrowth of Cutibacterium acnes and often treated with synthetic agents that may cause side effects and resistance. The increasing demand for therapeutics with improved safety profiles and natural alternatives has encouraged the exploration of herbal remedies, including robusta green coffee beans (Coffea canephora). This study aimed to evaluate the anti-acne activity of robusta coffee bean ethanol extract against C. acnes. The extract was prepared through maceration and subsequently evaluated using to phytochemical screening, thin layer chromatography, and in vivo testing on New Zealand rabbits. Results confirmed the presence of flavonoids, alkaloids, tannins, steroids, and triterpenoids. In vivo assays demonstrated that the 75% extract concentration achieved a 96.69% reduction of acne lesions, comparable to the positive control at 99.35%, while lower concentrations showed moderate activity. These findings highlight the potential of robusta coffee bean extract as a promising natural anti-acne agent. The study implies that robusta extract can be further developed into herbal-based dermatological formulations, although future research should focus on isolating active compounds and conducting clinical trials for broader application.